PERILAKU PUNCHING SHEAR PADA HUBUNGAN KOLOM BULAT DENGAN FLAT SLAB AKIBAT BEBAN TEKAN AKSIAL - Muhammad Zardi (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
The aim of the tests was to investigate the influence of concrete strength, the eccentricity of the column and the use of shear reinforcement in flat slabs on punching shear. The research specimens are 8 units of flat slabs. Flat slab size 1400 x 1400 mm2 with thickness of 120 mm. Flat slabs were connected with circular column with dimension 225 mm of diameter and 200 mm of height. Flat slabs were made in to 2 variations of concrete strength, e.i. 30 MPa and 60 MPa, 2 variations of shear reinforcement, e.i. without shear reinforcement and with shear reinforcement and 2 variations of eccentricity that, e.i. without eccentricity and with eccentricity. Each treatment has 1 specimen. Each specimen has 6 cylinder specimens. Cylinder specimens used as a concrete strength control for main specimen (flat slab). The tests showed that the concrete strength had a strong influence on punching shear strength. This is shown by capacity increase of 42.78%; 54.00%; 46.59% and 0.02%. The value is ratio between the maximum load of the specimens with 60 MPa and 30 MPa at the same eccentricity and the same shear reinforcement. The eccentricity of column reduce the capacity of punching shear. This is shown by 3 specimens decrease in capacity of 3.70%; 36.75% and 7.30%. Only 1 specimen that increase in capacity of 9.27%. The value is ratio between the maximum load of the specimens with 40 mm eccentricity and 0 mm eccentricity at the same compressive strenght and the same shear reinforcement. The use of shear reinforcement does not always increase the punching shear capacity. There are 2 observations that increased capacity (52.07% and 65.37% at the centric load) and 2 observations decreased capacity (0.12% and 4.92% at the eccentric load). The value is ratio between the maximum load on the specimens using shear reinforcement with the specimens that do not use shear reinforcement at the same compressive strenght and the same eccentricity.The use of shear reinforcement increase punching shear capacity of flat slab at the centric load condition. The use of shear reinforcement decrease punching shear capacity of flat slab at the eccentric load condition.